The tin can society - Warren, Peter (Screenwriter); Remender, Rick (Image Comics, 2026)
The Tin Can Society is a heartfelt and human look at the evolution of friendships across a lifetime, at disability and ableism, and the destructive power of fame. Johnny Moore is a world-famous tech mogul known as much for his work pioneering mobility aids for people with disabilities (like himself) as he is for moonlighting as the metal-suited vigilante, Caliburn. But when Johnny is found murdered and his suit stolen, his estranged childhood best friends reunite to solve the mystery of his murder. --